Kalnychenko O.A., Kalnychenko N. M. Jobs of translation studies history - Kalnychenko O. A.; Kalnychenko N. M. (Philological Treatises, 2020)
The paper discusses the following aims of Translation Studies History: introduction to the field of Translation Studies through its history; historical knowledge of the subject as a part of a scholar’s education; as means of evaluating new hypotheses; as leading to moderation in translation theory and as furthering unity within a complex subject.